Candesartan exhibits low intrinsic permeation capacity and affects buccal tissue viability and integrity: An ex vivo study in porcine buccal mucosa (2023)
Candesartan is a nonpeptide angiotensin II receptor blocker that selectively binds to angiotensin II receptor subtype 1. It is administered orally in its ester form (candesartan cilexetil). However, its poor aqueous solubility results in its low bioavailability; therefore, other routes of administration must be explored. The buccal mucosa has been extensively studied as an alternative route for drug delivery as it improves the bioavailability of drugs administered via the peroral route. Porcine buccal mucosa has been widely used as an ex vivo model to study the permeability of various diffusants; however, studies on candesartan are limited. This study aimed to evaluate the ex vivo permeation profile of candesartan and its effects on the viability and integrity of porcine buccal mucosa. Initially, we evaluated the viability, integrity, and barrier function of the buccal tissue before performing permeability tests using freshly excised tissues or tissues after 12 h of resection. Here, three indicators were used: caffeine, β-estradiol, and FD-20 penetration; mucosal metabolic activity, as determined using MTT reduction assay; and haematoxylin and eosin staining. Our results indicated that the porcine buccal mucosa preserved its viability, integrity, and barrier function before the permeation assay, allowing the passage of molecules with a molecular mass of less than 20 kDa, such as caffeine, but not β-estradiol and FD-20. Furthermore, we analyzed the intrinsic capacity of candesartan to diffuse through the fresh porcine buccal mucosa under two pH conditions. The concentration of candesartan in the receptor chamber of Franz diffusion cell was quantified using ultra-high liquid chromatography. In the permeation assay, candesartan exhibited a low intrinsic permeation capacity that impacted the buccal tissue viability and integrity, suggesting that using the buccal mucosa as an alternative route of administration requires developing a pharmaceutical formulation that reduces the adverse effects on mucosa and increasing the buccal permeability of candesartan.